RISK FACTORS ASSOCIATED WITH THE EVENT OF PROSTATE CANCER (CASE STUDY IN Prof. Dr. MARGONO SOEKARJO PURWOKERTO HOSPITAL) - Viva Ratih Bening Ati (Fakultas Kedokteran Universitas Jenderal Soedirman, 2021)
The incidence of prostate cancer (PCa) is closely related to increasing age and other factors such as family history, obesity, smoking habits, vasectomy history, and alcohol consumption. As the number of cases increases, understanding the risk factors associated with the incidence of PCa becomes very important. Therefore, this study was conducted to determine the risk factors for PCa in Prof. Dr. Margono Soekarjo Purwokerto’s Hospital as an approach to the identification and prevention of PCa events. Observational research using cased control was conducted at the Urology Surgery Polyclinic of Prof. Dr. Margono Soekarjo Purwokerto Hospital. 15 PCa patients and controls in the form of participants diagnosed with other cancers as many as 8 people. Univariate analysis using SPSS was conducted to determine the relationship of risk factors to the incidence of PCa with a significance of p<0.05. The results showed that some of the prominent characteristics of PCa respondents were age >60 years (66.7%), married (80%), not suffering from diabetes mellitus (93.3%), normal lifestyle (80%), and not consuming alcohol (100%). In the control group, age >60 years (62.5%), no family history of prostate cancer (100%), normal lifestyle (100%), and smoking (50%). From the results of the study, it was concluded that the characteristics of respondents in the case group were mostly aged > 60 years, had low education, worked as farmers, and had no history of prostate cancer in their family.